Analysing Classroom Management Strategies As the Main Pillar of Successful Student Learning Achievement : Menganalisis Strategi Pengelolaan Kelas Sebagai Pilar Utama Keberhasilan Prestasi Belajar Siswa - Amalia, Tiara; Na’imah, Na’imah; Azizah, Yulia Lutfiyani; Hidayatussa’adah, Hidayatussa’adah; Sadad, Roihan (STAI Publisistik Thawalib Jakarta, 2024)
Classroom management plays a crucial role in creating a learning environment that supports student learning outcomes. The research was conducted qualitatively through a documentation study, collecting previous research findings to analyze the pillars of classroom management that influence student learning. Data processing involved searching, filtering, assessing feasibility, and analyzing article content. The results of the study show: First, an effective learning community requires teachers to design learning spaces by considering student diversity, processes, and class structure to encourage participation, strengthen interaction, and improve learning outcomes. Second, managing teacher-student interactions creates a conducive atmosphere that supports the achievement of learning goals, character development, and positive relationships, which increases motivation and learning outcomes. Third, the use of varied teaching methods can enhance critical thinking skills, reduce boredom, and increase student engagement. Fourth, a comfortable and organized classroom atmosphere improves concentration, understanding, and retention of information. In conclusion, good classroom management can enhance student learning outcomes.